Los desastres no son naturales = Disasters are not natural - Hernández, Marvín; Romero, Edgar; Greenblatt, Susan Caren
An excellent photographic and textual history of physical disasters in El Salvador during the past century, with focus on how inattention to ecological factors have increased the impact of disasters. The work includes numerous photos on quality stock.